Problem Sosial Anak Putus Sekolah (Studi Kasus di Desa Lala Kabupaten Buru) - M. Rusdi; Astriyani A. Papuangan; Ismail; Radiatan Mardiah; Ariswildani Arifuddin (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2020)
Children who are dropping out of school are closely related to social welfare and become more critical to address immediately because the number of them is increasing day by day. The research objective is (1) To describe the socio-economic conditions of the dropping out of school children and solutions to overcome these problems, (2) To reveal the positive values contained in the social issues of children dropping out of school in Lala Village, Buru Regency. This research uses a descriptive qualitative design located in the village of Lala, Namlea, Buru Regency. The subjects were determined by purposive sampling technique, and data collection techniques were carried out by means of observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, verification, and drawing the conclusion. The socio-economic conditions of children dropping out of school in Lala Village, Buru Regency are seen from their socio-economic situation. They help their parents to work to fulfill their daily needs. Most of the parents of children dropping out of school work as fishermen, construction workers, and hawkers because the amount of basic needs is greater than the amount of income; moreover, they also had no job opportunities. The involvement of local governments, community leaders, and religious leaders in disseminating strategic policies regarding the importance of education and scholarship programs for children who cannot afford or excel is a solution in overcoming the number of children dropping out of school.